Methodology and Techniques for Highly-Precise Radar Cross Section Measurements at W-Band - Rachel E. Jarvis; Jay W. McDaniel (IEEE Access, 2022)
This paper explores the challenges of radar cross section (RCS) measurements at W-band and proposes several techniques to overcome these challenges to obtain an accurate RCS measurement. This paper combines $S_{11}$ measurements collected using traditional radio frequency (RF) hardware with post-processing algorithms to extract RCS values with a single antenna. Vector background subtraction and time-gating suppress unwanted reflections while increasing the system’s dynamic range capability. Experiments are conducted at the University of Oklahoma’s mm-Wave Laboratory with a Vector Network Analyzer (VNA) and frequency extender to evaluate the proposed measurement techniques. The setup is calibrated with a metal sphere, and the RCS of a smaller metal sphere and an arrangement of four spheres is extracted. The single sphere’s RCS is measured with a 0.304 dBsm average error, and the distributed object under test (OUT) RCS is measured with a 1.60 dBsm average error from 80-90 GHz. Each OUT is placed on a 3D-printed pedestal, and the remainder of the test hardware is part of an existing mm-Wave antenna measurement configuration. The post-processing clutter cancellation techniques enable a flexible test configuration to isolate the OUT RCS without purchasing specialized hardware.